Heritage trees in the Philippine urban landscapes an assessment of their selected socio-cultural, ecological and conservation values - Aquino-Ong, Susan C (University of the Philippines Los Baños, 2012)
Selected, ecological, socio-cultural and, conservation values of Heritage Trees (HTs) in urban landscapes located in the cities of Quezon, Legaspi, Cebu and Davao in four climatic types in the Philippines were assessed. Ecological values measured were temperature and humidity differences under and outside canopies of HTs. Carbon sequestration of HTs was also estimated. Socio-cultural and conservation values were assessed involving a survey of 200 respondents using Likert scale and the modified Linear Arousal-Stress Scale (LASS). Twelve interdisciplinary experts used the Analytic Hierarchy Process (AHP) to rank criteria for valuing HTs. Data were triangulated by field interviews, remote sensing of secondary documents. T-test, Analysis of Variance and the Statistical Package for Social Research were used in data analyses. Results indicated that 99 percent of the respondents prefer to retain urban HTs and were aware of their healthy existence. Albizia saman ((Jacquin) Merrill) or akasya was the most known HT in urban areas due to its dominant canopy and prevalence in public spaces, followed by Balete (Ficus sp.) and Narra (Pterocarpus indicus). Between 8 a.m. to 4 p.m., the mean ambient temperatures under the canopy of HTs were cooler by 3.94 °C (range=3.85-4.05°C) while mean humidity was higher by 8.92 percent (range=6.04-10.69%). Between 12 p.m. to 3 p.m., the mean temperature and mean humidity differences under and outside canopies were - 4.09°C and +8.5 percent, respectively. These values were the presumed maximum benefits that shades of HTs provide on the hottest time of the day. During the same period, the 10-point LASS scale illustrated what respondents felt when under a canopy and had a weighted mean of 9.41 level of comfort compared to only 1.30 when under sunlit-exposed areas. These results provide the physical basis of respondents' perception, of what maginhawa and maalinsangan are, implying that 81.10 percent is contributed as the perceived level of comfort when respondents stay under the shade and canopy of HTs. Using the Likert scale, respondents perceived ecological values as the most important value of HTs (mean=4.24) whereas experts ranked socio-cultural values as highest when using the AHP method. The normalized values from Likert scale was computed and compared with AHP values. Results indicate that the public gave equal weights to the three values whereas experts highly preferred the socio-cultural values. A major contribution of this research is that HTs can be assessed objectively and that decision-and policy-makers in various institutions can use the combined methods to resolve conflicts about the fate of HTs in urban landscapes. A modified set of assessment criteria for identifying and selecting HTs for conservation is also proposed.